Impact of T-ACASI on Survey Measurements of Subjective Phenomena - Harmon, Thomas (Oxford University Press, 2009)
Numerous studies have shown that audio-computer-assisted self-interviewing (audio-CASI) and telephone audio-CASI (T-ACASI) technologies yield increased reporting of sensitive and stigmatized objective phenomena such as sexual and drug use behaviors. Little attention has been given, however, to the impact of these technologies on the measurement of subjective phenomena (attitudes, opinions, feelings, etc.). This article reports results for the seven subjective measurements included in the National STD and Behavior Measurement Experiment (NSBME). NSBME drew probability samples of USA and Baltimore adults (Ns = 1,543 and 744, respectively) and randomized these respondents to be interviewed by T-ACASI or telephone interviewer-administered questioning (T-IAQ). Response distributions for all subjective measurements obtained by T-ACASI diverge from those obtained by human telephone interviewers. For six of our seven ordinal-scaled measurements, this divergence involved shifting responses directionally along the ordinal scale, as opposed to a nondirectional redistribution among response categories. When interviewed by T-ACASI, respondents were more supportive of traditional gender roles and corporal punishment, less supportive of integrated neighborhoods and same-gender sex, and more likely to agree that occasional marijuana use is harmless and to describe themselves as attractive. The majority of these results suggest that telephone survey respondents may provide more “tolerant” and “socially liberal” responses to human interviewers than to a T-ACASI computer. Similarly, although the evidence is not entirely consistent, the impact of T-ACASI appears to increase with the social vulnerability of the population surveyed.